EXAM 1 Calc - Version 097 – Exam 1 – gualdani –(56410...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Version 097 – Exam 1 – gualdani – (56410) 1 This print-out should have 20 questions. Multiple-choice questions may continue on the next column or page – find all choices before answering. 001 10.0 points Below is the graph of a function f . 2 4 6 − 2 − 4 − 6 2 4 6 8 − 2 − 4 Use the graph to determine lim x → 2 f ( x ) . 1. limit = 5 2. limit = 4 3. limit = 6 4. limit = 2 5. limit does not exist correct Explanation: From the graph it is clear the f has a left hand limit at x = 2 which is equal to 6; and a right hand limit which is equal to 4. Since the two numbers do not coincide, the limit does not exist . 002 10.0 points When f is the function defined by f ( x ) = braceleftbigg 3 x − 7 , x ≤ 1 , 5 x − 8 , x > 1 , determine if lim x → 1+ f ( x ) exists, and if it does, find its value. 1. limit does not exist 2. limit = − 3 correct 3. limit = − 2 4. limit = 0 5. limit = − 1 6. limit = − 4 Explanation: The right hand limit lim x → 1+ f ( x ) depends only on the values of f for x > 2. Thus lim x → 1+ f ( x ) = lim x → 1+ 5 x − 8 . Consequently, limit = 5 × 1 − 8 = − 3 . 003 10.0 points Determine lim x → 6 √ x + 3 − 3 x − 6 . 1. limit = 3 2. limit = 1 6 correct 3. limit = 6 4. limit doesn’t exist 5. limit = 1 3 Version 097 – Exam 1 – gualdani – (56410) 2 Explanation: After rationalizing the numerator we see that √ x + 3 − 3 = ( x + 3) − 9 √ x + 3 + 3 = x − 6 √ x + 3 + 3 . Thus √ x + 3 − 3 x − 6 = 1 √ x + 3 + 3 for all x negationslash = 6. Consequently, limit = lim x → 6 1 √ x + 3 + 3 = 1 6 . 004 10.0 points Determine lim h → f (1 + h ) − f (1) h when f ( x ) = 4 x 2 + 3 x + 5 . 1. limit does not exist 2. limit = 8 3. limit = 11 correct 4. limit = 10 5. limit = 9 6. limit = 7 Explanation: Since f (1 + h ) − f (1) = 4(1 + h ) 2 + 3(1 + h ) + 5 − 12 = 11 h + 4 h 2 = h (11 + 4 h ) , we see that lim h → f (1 + h ) − f (1) h = lim h → h (11 + 4 h ) h . Consequently, limit = 11 . 005 10.0 points Determine if the limit lim x → sin 6 x 7 x exists, and if it does, find its value. 1. limit = 7 2. limit = 6 7 correct 3. limit = 6 4. limit = 7 6 5. limit doesn’t exist Explanation: Using the known limit: lim x → sin ax x = a , we see that lim x → sin 6 x 7 x = 6 7 . 006 10.0 points After t seconds the displacement, s ( t ), of a particle moving rightwards along the x-axis is given (in feet) by s ( t ) = 2 t 2 − 2 t + 5 ....
View Full Document

This note was uploaded on 10/08/2010 for the course MATH 408K taught by Professor Gualdani during the Fall '09 term at University of Texas.

Page1 / 10

EXAM 1 Calc - Version 097 – Exam 1 – gualdani –(56410...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online